Social & Economic Implications of Universal Service Obligation Fund - Garg, Vinod Kumar; Singh, Amarjit (Indian Journal of Marketing, 2008)
The Government of India is committed to provide access to all people for basic telecom services at affordable and reasonable prices. Keeping in view the development of telecom facilities in rural areas, the universal obligatory fund had been established. The resources for meeting the USO would be raised through a ’universal access levy’ which would be a percentage of the revenue earned by all the operators under various licenses. The percentage of revenue share towards universal access levy would be decided by the Government in consultation with TRAI. The implementation of the USO obligation for rural/remote areas would be undertaken by all fixed service providers who shall be reimbursed from the funds from the universal’ access levy. Other service providers shall also be encouraged to participate in USO provision subject to technical feasibility and shall be reimbursed from the funds from the universal access levy.